Regional differences in the Association of Healthy Aging with the incidence of falls: an analysis based on the China Health and Retirement Longitudinal Study from 2011 to 2020 - Xiang Li; Xiang Li; Chao Wei; Kejing Hu; Jie Sun; Xiang Gao; Jianhong Yang (Frontiers Media S.A., 2024)
BackgroundFalls frequently occur among the older adult population. In this study, we examined the variations in fall incidence across different regions over time, focusing on the disparities between urban and rural areas among older adult Chinese individuals, Healthy aging is comprised of five dimensions: (1) absence of chronic diseases, (2) good physical functioning, (3) normal cognitive function, (4) active social participation, and (5) absence of depression. Additionally, we explored the relationship between healthy aging and the occurrence of falls in middle-aged and older adults. Falls are defined as events that occurred within the past two years.ResultsAmong 9,918 participants, 33.8% lived in urban areas and 23.0% achieved healthy aging. In contrast, 66.2% resided in rural areas with 16.5% achieving healthy aging. In 2011, rural residents had a higher fall incidence rate (17% in rural vs. 13.5% in urban); by 2020, the fall rate remained higher in rural areas (19.5% in rural vs. 17.3% in urban). Unhealthy aging (HR = 1.08, 95%CI: 1.00-1.16) were risk factors for falls. Subgroup analysis revealed that in rural areas, unhealthy aging increased the risk of falls. In urban areas, the increased risk of falls associated with unhealthy aging was not significant (Rural HR = 1.11, 95%CI:1.01-1.22; Urban HR = 1.05, 95%CI: 0.93-1.18).ConclusionHealthy aging may be more strongly associated with a lower risk of falls in rural areas, while this association might be less pronounced in urban areas due to different environmental and social factors. This highlights the need for environment-specific fall prevention strategies and targeted measures for the older adult.